Policy Response, Local Service Delivery, and Governance in Bangladesh, Nepal, and Sri Lanka
XVII, 266 p. 14 illus.
Keywords: This book analyzes contemporary issues in governance, policy management, and policy performance both at the central and local levels in Bangladesh, Nepal, and Sri Lanka. The focus is on some central social issues such as empowerment, the inclusion of minorities, institutional trust, policy implementation, and local service delivery. Although these three countries have recently opted for democratic governance, the journey to establish and consolidate democracy as well as enhance governance capacity have been painful and filled with challenges. The chapters in this volume are country specific studies based on empirical data both quantitative and qualitative collected for several years and presented in readable prose. This does not, however, rule out the general applicability of the findings to other contexts within and beyond the borders of these countries. Despite huge differences in South Asia, the policy and governance issues and challenges that are explored, highlighted, and analyzedalso have commonalities with other South Asian countries. Ishtiaq Jamil, Professor, Department of Administration and Organization Theory, University of Bergen, Norway. Tek Nath Dhakal, Professor, Central Department of Public Administration, Tribhuvan University, Kathmandu, Nepal. Sk Tawfique M Haque, Professor and Director, South Asian Institute of Policy and Governance (SIPG),North South University, Dhaka, Bangladesh. Laxmi Kanta Paudel, Lecturer, Central Department of Public Administration,Tribhuvan University, Kathmandu, Nepal. Hasan Muhammad Baniamin, Assistant Professor, South Asian Institute of Policy and Governance (SIPG), North South University, Dhaka, Bangladesh.